Antibiotic resistance pattern and virulence genes content in avian pathogenic Escherichia coli (APEC) from broiler chickens in Chitwan, Nepal - Manita Subedi; Himal Luitel; Bhuminanda Devkota; Rebanta Kumar Bhattarai; Sarita Phuyal; Prabhat Panthi; Anil Shrestha; Dhiraj Kumar Chaudhary (BMC Veterinary Research, 2018)
Abstract Background Avian pathogenic Escherichia coli (APEC) are causative agent of extraintestinal infections, collectively known as colibacillosis, which results significant losses in poultry industries. The extraintestinal survival of E. coli is facilitated by numerous virulence factors which are coded by virulence genes. This study was conducted to find out the pattern of antibiotic resistance and virulence genes content in the APEC strains isolated from broiler chickens at National Avian Disease Investigation Laboratory and Veterinary Teaching Hospital, Rampur, Chitwan, Nepal. Results A total of 50 E. coli strains were isolated from 50 colibacillosis suspected broiler chickens. Out of 50 isolates of E. coli, 47 (94%) showed resistant to three or more antimicrobials. The highest levels (22%) of multidrug-resistant E. coli were observed for five different types of antimicrobials. Antibiogram profiles of 50 E. coli strains showed the maximum resistance to ampicillin (98%), followed by co-trimoxazole (90%), and doxycycline (62%). The highest intermediate resistance was shown by colistin (50%) and the highest sensitivity was against amikacin (84%), followed by nitrofurantoin (55%). Based on the genetic criteria, 45 (90%) E. coli isolates were considered as pathogenic (APEC) which contained more than five virulence genes. Out of total APEC genes detected, we found the combination of iss, iucD, hlyF, ompT, iroN, and iutA genes were mostly associated with the APEC and additionally, to some lesser extent irp2, papC, Cva/cvi, and tsh genes showed the critical role for virulent traits of APEC strains. Conclusion In this study, high prevalent of antimicrobial resistant pattern was found with avian pathogenic E. coli strains isolated from broiler chickens. To our knowledge, this is the first molecular analysis which confirmed the prevalence of APEC strains in poultry sector in Nepal. These finding suggest the need of surveillance and intervention system to control misuse of antibiotics and APEC outbreak in the poultry farm.